Novel variants of NEK9 associated with neonatal arthrogryposis: Two case reports and a literature review - Liu, Fang; Dai, Liying; Li, Zhi; Yin’s, Xiaowei (Frontiers in Genetics, 2023)
Background: Gene mutation can cause congenital joint contractures or arthrogryposis, here we report the clinical phenotype and genetic analysis of two Chinese infants with congenital joint contractures. Methods: Using Illumina NovaSeq 6000 series sequencer (PE150), whole-exome sequencing (WES) and whole genomic copy number variation were performed for the probands and their parents. Results: Patient 1 presented mild-moderate form of contractures involving the hands, elbows, hips, knees; neck stiff; camptodactyly of the fingers; subtle facial dysmorphism, atrial septal defect, patent ductus arteriosus and pyloric stenosis. Genetic analysis identified the novel compound heterozygous variation in NEK9: c.717 C>A(p.C239*741) and c.2824delA, p.M942Cfs*21. The c.717 C>A( p.C239*741) resulted in premature termination of protein translation and eliminating the final 741 amino acids. The mutation of c.2824delA located in the last domain of the peptide chain, it is presumed to have some effect on the stability of protein structure. The patient 2 presented with mild-moderate form of contractures involving the elbows, hips, knees, he had atrial septal defect and mild pulmonary stenosis. Genetic analysis revealed that he carried a compound heterozygous variation in NEK9, one variation was the same as patient 1 (c.2824delA, p.M942Cfs*21), the other was c.61 G>T, p.E21*959, this mutation cause premature translation termination, thereby affect their function. Conclusions: According to previous literature reports, the patients involved were either stillbirths or juvenile patients, this is the first reports about NEK9-related arthrogryposis in neonatal patients. This study expands the clinical phenotype spectrum and gene spectrum of NEK9-associated arthrogryposis.